Pola Asuh Otoriter Orang Tua, Kecerdasan Emosi, dan Kemandirian Anak SD - Hidayati, Nur Istiqomah (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2014)
Abstract. The purpose of the research is to know the correlation between Authoritarian Parenting, student’s Emotional Intelligence with Student’s autonomy. Subjects of the research are 70 person of Elementary School Students grade fifth (5th ) in gugus IV area, Merakurak district, Tuban regency. Data were collected by scales of Authoritarian Parenting, student’s Emotional Intellegence and Student’s self control The partial correlation. The data analysis used multiple regression analysis and than partial correlations. Results of multiple regression analiysis showed that the Authoritarian Parenting and student’s Emotional Intellegence have a significant relation with students’ autonomy. The partial correlation of Authoritarian Parenting and students’ autonomy have a significant correlation to negative side. The partial correlation of Emotional Intellegence and students’ autonomy have a significant correlation to positive side. Authoritarian parenting and student’s emotional intelligence give effective contibution to Student’s autonomy about 55,2 %. Keywords: Authoritarian parenting, emotional intelligence, students’ autonomy.